Economic Burden of Cervical and Head and Neck Cancer in Taiwan from a Societal Perspective - Wu, Ying-Hui; Lai, Chyong-Huey; Chien, Ling; Pan, Yun-Chung; Lin, Yu-Jr; Feng, Casey; Chang, Chee-Jen (International journal of environmental research and public health, 2023)
Background: Head and neck cancers (HNC) are increasingly recognized as important human papillomavirus (HPV)-related malignancies in addition to cervical cancer (CC). However, data on the socioeconomic impact of HNC and CC in Taiwan are limited. Methods: A retrospective cohort study was conducted to estimate the total direct medical cost and indirect productivity loss from CC and HNC between 2014 and 2015. Patient data from the Taiwan National Cancer Registry were analyzed, with matched non-cancer controls from the Taiwan National Healthcare Reimbursement Database. Indirect costs due to premature deaths were calculated using public data from Taiwanese government reports. Results: In the direct cost analysis, 2083 patients with newly diagnosed CC and 11,078 with newly diagnosed HNC (10,036 males) were identified between 2014 and 2015 and followed up through the end of 2016 or until death. The total direct medical costs incurred in 2014 and 2015 due to HNC were 11.54 times higher in males than in females, and 4.55 times higher than CC. Indirect cost analysis showed the total annual productivity loss was New Taiwan Dollar (NTD) $12 billion in 2019, and 79.99% was attributed to male HNC. Conclusion: In Taiwan, the socioeconomic burden associated with male HNC is high and greater than that seen with CC. While not all HNCs are attributable to HPV infection, prevention of HNC through HPV vaccination should be considered for both sexes.